Rancang Bangun Sistem Manajemen Banner Periklanan pada PT. Merah Putih Media Menggunakan Framework Laravel Berbasis Web dan Metode RAD - Ahmad Rifki Fachrudin; Galuh Saputri (Institut Sains dan Teknologi Nasional, 2023)
Abstract Banner Advertising Management System at PT. Merah Putih Media is designed to facilitate the management of advertising banner data on online media owned by companies. The aim of this research is to design and build an efficient, easy-to-use banner advertising management system. This study uses the Laravel Framework as a development basis and the RAD Method to speed up the system development process. In system development, the RAD method allows for rapid prototyping and testing so that the results can be evaluated immediately. The system consists of banner ad data management and user management modules. The banner ad data management module is used to manage banner ad data on online media, while the user management module is used to manage system users. The result of this research is a banner advertising data management system to manage banner advertising data at PT. Merah Putih Media. This system effectively and efficiently manages advertising banners on online media and can help PT. Merah Putih Media in improving company performance. Keywords: laravel, banner ads, php, framework, bootstrap, RAD.